A New Research about Pion Parton Distribution Function - 楼立洋 阮建红 (Chinese physics letters, 2015)
A new fit of the pion parton distribution functions is provided. Only valence quark distributions are used at a low evolution scale and are evolved with the modified Dokshitzer- Gribov-Lipatov-Altarelli-Parisi equation which is briefly introduced in this work, and the sea quark and gluon distributions are only generated by the quantum chromodynamics processes. We find that the patton distributions can explain the pion-nucleon experiments data well, and it can also be compared with the data from the leading neutron data of experiments at HERA. The momentum distributions among the partons are discussed and our results are consistent with some models.